MEMAHAMI PESAN MORAL AL-QUR’AN (Studi Terhadap Konsep Gharad Dalam Tafsir Al-Mizan) - Kusnadi Kusnadi (Wardah, 2014)
This article explores consept purpose (gharad) in thabathaba’i perpective to understand message of al-Quran. As speech of Good, thabathaba’i think that Al-Qur’an must possess unity. Unity of the aims and meaning. Unity of meaning interpreted that the main purpose of the Qur'an which leads to the path of truth. As the rule, thabathaba’i conclude that the gharad of a surah important enough to basic interpretation and understand Al-qur’an.